Prevalence of diarrhea of goats and their concurrent blood profile in north west region of Bangladesh (Asian Journal of Medical and Biological Research, 2021)
In Bangladesh, Diarrhea occurs in goats of any age and is responsible for poor growth in kids and a significant loss of production both through morbidity and mortality. The study was undertaken to determine the clinical prevalence of diarrheal diseases of goats with concurrent blood profile. A total of 1,007 goats were examined which were brought for treatment in the Upazilla Veterinary Hospital, Biral, Dinajpur. Among them 149 goats were found clinically affected by diarrhea and the overall prevalence of diarrheal disease in goats was 14.80%. A total of 402 male and 605 female goats were examined and their diarrheal prevalence were 14.17%, 15.15%, respectively. The Prevalence in Jamnapari goat (18.80%) was signicantly (P